The big ugly [videorecording (DVD)] - Wiper, Scott; Wiper, Scott; Wiper, Scott; Jones, Vinnie, 1965-; Jones, Vinnie, 1965-; McDowell, Malcolm, 1943-; Perlman, Ron, 1950- (Lionsgate, 2020)
When a British crime syndicate enforcer travels with his boss to West Virginia and discovers that his girlfriend is missing, he seeks revenge against an oil businessman's son.